Geotechnical and Geological Engineering - Geotechnical and Geological Engineering (Springer Nature, 2026)
Geotechnical and Geological Engineering publishes papers in the areas of soil and rock engineering and also of geology as applied in the civil engineering, mining and petroleum industries. The emphasis is on the engineering aspects of soil and rock mechanics, geology and hydrogeology, although papers on theoretical and experimental advances in ground mechanics are also welcomed for inclusion.
FI 0.44
Q3
Keywords: Earth; Space & Environmental Sciences; Geology & Geophysics; Geofísica; Acuerdos transformativos; Transformative agreements; Ingeniería; Suelos; Rocas; Geología aplicada